2012
DOI: 10.1016/j.bbmt.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Cost-Effectiveness of Hematopoietic Cell Transplantation

Abstract: Interest is growing in economic and comparative effectiveness analyses, with increasing emphasis on optimizing healthcare resources and costs. Limited information is available on the economic aspects of hematopoietic cell transplantation (HCT). We review contemporary literature on the costs and cost-effectiveness of HCT in the United States and worldwide. Published studies confirm the high costs associated with HCT, although the reported costs are highly variable, related to the differing methodologies used ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 29 publications
4
53
0
2
Order By: Relevance
“…on June 7, 2019. by guest www.bloodjournal.org From analyses,time horizons, and study methods, as has been reported by prior reviews of literature in this area. 55,56 Most studies have focused on the early costs after transplantation until 100 days or 1 year; cost studies beyond 1 year are rare. Investigators have shown that, similar to the clinical outcomes, the costs of procedures are influenced by patient-and disease-related factors, transplantationrelated factors, and external factors.…”
Section: Costs Of Hct 1549mentioning
confidence: 99%
“…on June 7, 2019. by guest www.bloodjournal.org From analyses,time horizons, and study methods, as has been reported by prior reviews of literature in this area. 55,56 Most studies have focused on the early costs after transplantation until 100 days or 1 year; cost studies beyond 1 year are rare. Investigators have shown that, similar to the clinical outcomes, the costs of procedures are influenced by patient-and disease-related factors, transplantationrelated factors, and external factors.…”
Section: Costs Of Hct 1549mentioning
confidence: 99%
“…5,6 Use of hematopoietic cell transplantation (HCT) as a treatment modality for many hematologic malignancies and some solid tumors has continued to grow, highlighting areas for further development and unmet need. [7][8][9][10] In this article, we review coordination problems unique to patients treated with HCT and identify pertinent stakeholders throughout the continuum of care. We describe the existing care coordination models and propose a framework for a coordination model for HCT using components from existing models to appropriately meet the complex needs of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although cost effectiveness of hematopoietic cell transplantation has been described, 33 such perspectives rely on single institution experiences. Identifying the origin of hospital charges in expensive procedures such as SCT is the first step in cost containment.…”
Section: Strengths and Limitationsmentioning
confidence: 99%